Model for Peruvian industrialization in a competitive world - Aranaga Manrique, David (2005)
At the beginning of this century, Peruvian industrialization is once again a reason for deep reflection. We need an industry that drives the economic growth of the country in the current process of world globalization, builds dynamic competitive advantages and promotes a greater participation of our qualified human resources through companies, to face the process of change that is being experienced in the international economic relations.